Impact of Mathematics Anxiety on Secondary School Students’ Learning Achievement - B.C., Gopal (Journal of Educational Research and Innovation, 2025)
Mathematics anxiety is widely recognized as an emotional, rather than a psychological, problem affecting factor influencing students’ performance in mathematics It has established significance attention in literature, yet there remains remarkable uncertainty regarding variables involved. This study examines the level of mathematics anxiety and its impact on secondary school students’ learning achievement. Using a correlation survey design, data was collected through mathematics achievement test and mathematics anxiety scale with grade 10 students in community schools of surkhet District. The collected data was analyzed using Pearson correlation. The findings reveal that the status of mathematical anxiety to be found moderate level (83.7%). Moreover, there is significant relationship between students’ mathematics anxiety and their learning achievement indicating that mathematics anxiety is affecting factor of students’ learning achievement. The study offers that school level remedial math anxiety intervention for enhancing learning achievement of secondary school students.